Intra-rater and Inter-rater Reliability of the KangaTech (KT360) Fixed Frame Dynamometry System During Maximal Isometric Strength Measurements of the Knee Flexors. - Ellie Woolhead; Richard Partner; Megan Parsley; Ashley Jones (International Journal of Sports Physical Therapy)
# Background